Metabolic syndrome in Peru: Analysis of a national health survey in 2017-2018 - Guzmán-Vilca, Wilmer Cristóbal (2024)
Aim: Metabolic syndrome increases the risk of diabetes and cardiovascular disease. Recent studies on the prevalence of metabolic syndrome in Peru have focused on specific populations without national representativeness. Material and Methods: Cross-sectional analysis of a national health survey. Metabolic syndrome was defined according to the criteria of the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) and the International Diabetes Federation (IDF). The prevalence of metabolic syndrome was described according to sociodemographic variables, as well as its most frequent individual components and their predicted cardiovascular risk. Results: We included 917 participants aged 18-59 years. The prevalence of metabolic syndrome was 46% according to the NCEP ATP III criteria and 57% according to the IDF criteria. According to both criteria, prevalence of metabolic syndrome was higher in women, people aged 40-59 years, and people from urban areas. ~60% of the population with metabolic syndrome met 3 criteria, and 96% had low HDL, 79% hyperglycemia, and 77% abdominal obesity. The predicted cardiovascular risk was higher in those meeting all 5 criteria (3,9%) than 3 criteria (1.8%). Conclusions: Metabolic syndrome affects 1 in 2 adults in Peru and is more frequent in women, older people, and urban population. Of every 10 Peruvians with metabolic syndrome, 6 meet 3 components and only 1 meet all 5 components. The most frequent components are low HDL, hyperglycemia, and abdominal obesity.